Amino acid changes in PB2 and HA affect the growth of a recombinant influenza virus expressing a fluorescent reporter protein - Katsura, Hiroaki (Sci Rep, 2016)
Influenza viruses that express reporter proteins are useful tools, but are often attenuated. Recently, we found that an influenza virus encoding the Venus fluorescent protein acquired two mutations in its PB2 and HA proteins upon mouse adaptation. Here, we demonstrate that the enhanced viral replication and virulence in mice of this Venus-expressing influenza virus are primarily conferred by the PB2-E712D mutation, with only a minor contribution by the HA-T380A mutation.